2020
DOI: 10.1111/mmi.14508
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenes SpxA1 is a global regulator required to activate genes encoding catalase and heme biosynthesis enzymes for aerobic growth

Abstract: An imbalance of cellular oxidants and reductants causes redox stress, which must be rapidly detected to restore homeostasis. In bacteria, the Firmicutes encode conserved Spx‐family transcriptional regulators that modulate transcription in response to redox stress. SpxA1 is an Spx‐family orthologue in the intracellular pathogen Listeria monocytogenes that is essential for aerobic growth and pathogenesis. Here, we investigated the role of SpxA1 in growth and virulenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
43
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(47 citation statements)
references
References 52 publications
4
43
0
Order By: Relevance
“…These results may explain why the mutant strain is more sensitive to hydrogen peroxide. Previous work showed that the analogous genes were also downregulated in spxA1 deletion mutant and these mutant strains were more sensitive to hydrogen peroxide in Streptococcus sanguinis and Listeria monocytogenes than wild-type strains (Chen et al, 2012;Cesinger et al, 2020). The mechanism by which BprR protein regulates these genes remains unclear, and further work is still needed to provide an adequate explanation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results may explain why the mutant strain is more sensitive to hydrogen peroxide. Previous work showed that the analogous genes were also downregulated in spxA1 deletion mutant and these mutant strains were more sensitive to hydrogen peroxide in Streptococcus sanguinis and Listeria monocytogenes than wild-type strains (Chen et al, 2012;Cesinger et al, 2020). The mechanism by which BprR protein regulates these genes remains unclear, and further work is still needed to provide an adequate explanation.…”
Section: Discussionmentioning
confidence: 99%
“…Both SpxA1 and SpxA2 are closely related to the oxidative stress responses of B. anthracis , and spxA1 is essential for peroxide resistance and participates in disulfide stress tolerance ( Barendt et al, 2013 , 2016 ). SpxA1 is also involved in oxidative stress response of many gram-positive bacteria ( Chen et al, 2012 ; Kajfasz et al, 2017 ; Nilsson et al, 2019 ; Cesinger et al, 2020 ). For example, Chen et al (2012) reported that SpxA1 is a global regulator required to activate genes encoding catalase in Listeria monocytogenes , and Nilsson et al (2019) also reported that SpxA1 is involved in the oxidative stress response in Streptococcus mutans .…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, bacteria were grown overnight in BHI shaking at °C and subcultured to an optical density at nm (OD 600 ) of 0.02 into 25 mL BHI. [51]. Results were evaluated using CLC Genomics Workbench (Qiagen) and transcripts that were changed >2-fold (p < .01) were included in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In Intracellular growth curves. Growth curves in bone marrow-derived macrophages (BMMs) were performed as previously described [51], with the following modifications.…”
Section: Discussionmentioning
confidence: 99%
“…Both SpxA1 and SpxA2 are closely related to the oxidative stress responses of B. anthracis, and spxA1 is essential for peroxide resistance and participates in disulfide stress tolerance (Barendt et al, 2013(Barendt et al, , 2016. SpxA1 is also involved in oxidative stress response of many grampositive bacteria (Chen et al, 2012;Kajfasz et al, 2017;Nilsson et al, 2019;Cesinger et al, 2020). For example, Chen et al (2012) reported that SpxA1 is a global regulator required to activate genes encoding catalase in Listeria monocytogenes, and Nilsson et al (2019) also reported that SpxA1 is involved in the oxidative stress response in Streptococcus mutans.…”
Section: Discussionmentioning
confidence: 99%